Firmicutes-enriched IS1447 represents a group of IS3-family insertion sequences exhibiting unique + 1 transcriptional slippage - Ya-Jun Liu; Kuan Qi; Jie Zhang; Chao Chen; Qiu Cui; Yingang Feng (Biotechnology for Biofuels, 2018)
Abstract Background Bacterial insertion sequences (ISs) are ubiquitous mobile genetic elements that play important roles in genome plasticity, cell adaptability, and function evolution. ISs of various families and subgroups contain significantly diverse molecular features and functional mechanisms that are not fully understood. Results IS1447 is a member of the widespread IS3 family and was previously detected to have transposing activity in a typical thermophilic and cellulolytic microorganism Clostridium thermocellum. Phylogenetic analysis showed that IS1447-like elements are widely distributed in Firmicutes and possess unique features in the IS3 family. Therefore, IS1447 may represent a novel subgroup of the IS3 family. Unlike other well-known IS3 subgroups performing programmed − 1 translational frameshifting for the expression of the transposase, IS1447 exhibits transcriptional slippage in both the + 1 and − 1 directions, each with a frequency of ~ 16%, and only + 1 slippage results in full-length and functional transposase. The slippage-prone region of IS1447 contains a run of nine A nucleotides following a stem-loop structure in mRNA, but mutagenesis analysis indicated that seven of them are sufficient for the observed slippage. Western blot analysis indicated that IS1447 produces three types of transposases with alternative initiations. Furthermore, the IS1447-subgroup elements are abundant in the genomes of several cellulolytic bacteria. Conclusion Our result indicated that IS1447 represents a new Firmicutes-enriched subgroup of the IS3 family. The characterization of the novel IS3-family member will enrich our understanding of the transposition behavior of IS elements and may provide insight into developing IS-based mutagenesis tools for thermophiles.